2022
DOI: 10.1016/j.bioorg.2021.105587
|View full text |Cite
|
Sign up to set email alerts
|

In vitro potential antiviral SARS-CoV-19- activity of natural product thymohydroquinone and dithymoquinone from Nigella sativa

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Recently, we discovered the Dithymoquinone as potential anti-Covid-19 with MIC in range of nano-Molar [63] . Interestingly, we compare the pharmacophore site of the Dithymoquinone (dO1-O2 = 4.5 A) and the combined antibacterial/antiviral pharmacophore site of compound 4b (dO1-O2 = 4.6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we discovered the Dithymoquinone as potential anti-Covid-19 with MIC in range of nano-Molar [63] . Interestingly, we compare the pharmacophore site of the Dithymoquinone (dO1-O2 = 4.5 A) and the combined antibacterial/antiviral pharmacophore site of compound 4b (dO1-O2 = 4.6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Thymoquinone (THY) is one of the major constituents (28–57%) of black seed ( N. sativa ) oil. It has different biological activities, including cytotoxic, anti-inflammatory, anti-microbial, anti-viral, anti-oxidant, immune-stimulant, and anticoagulant effects [ 43 ]. Moreover, it has the ability to reduce the levels of pro-inflammatory mediators (ILs 2, 4, 6, and 12) and increases INF-γ [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DTQ has shown the potential to inhibit the viral-host interaction for the SARS-CoV-2 infection [ 47 ]. Esharkawy et al [ 48 ] checked the vitro anti-SARS-CoV-2 activity of DTQ and thymohydroquinone. They found that DTQ showed an IC 50 value of 275.2 ng/mL against SARS-CoV-2-infected cells; however, it was cytotoxic against uninfected VERO-E6 cells.…”
Section: Resultsmentioning
confidence: 99%